THE IMPLEMENTATION OF DIGITAL APPLICATIONS IN ENGLISH LANGUAGE TEACHING: A GLOBAL PERSPECTIVE - Irfun (International Journal of Teaching and Learning, 2026)
This study examines the impact of digital applications on English language teaching (ELT), synthesizing recent empirical research to evaluate their effectiveness, benefits, and challenges in enhancing language skills. Employing a qualitative review of peer-reviewed studies from 2023 to 2025, the findings reveal significant improvements in vocabulary (88%), grammar (80%), speaking (60%), and listening (50%) facilitated by adaptive, interactive, and multimedia-rich platforms. Immersive technologies like virtual and augmented reality and AI-powered personalized feedback further boost learner engagement and autonomy. Nonetheless, barriers such as unequal access to technology, varying digital literacy levels, and inadequate teacher preparation affect optimal use. The discussion highlights the importance of integrating technological innovation with sound pedagogical principles, emphasizing the need for institutional support to ensure equity and readiness. The study concludes that digital applications possess transformative potential for ELT, but strategic implementation and professional development are critical to maximizing their educational impact and preparing learners for 21st-century global communication.